Mycobacterium interjectum as Causative Agent of Cervical Lymphadenitis - De Baere, Thierry (American Society for Microbiology, 2001)
A mycobacterial strain isolated from a lymph node of a 3-year-old female with cervical lymphadenitis was identified as Mycobacterium interjectum by means of sequencing of the 16S rRNA gene. Analysis of this case and previously published cases demonstrates the importance of M. interjectum as a causative agent of cervical lymphadenitis in young children.